Toward a national participation index for developing countries in the global value chains: A graph theoretic modelling approach. (14th May 2018) - Ahmed, Faisal; Kumar, Pravin
Abstract : Purpose: The purpose of this paper is to identify factors which influence participation of developing countries in the global value chains (GVC) and to present a mathematical modeling technique to calculate a "National Participation Index of a developing country in the GVC" (hereinafter referred to as G-NPI). Design/methodology/approach: The paper identifies 17 factors, encompassing both country-specific and firm-specific considerations that influence a developing countries' participation in the GVCs. These factors have been grouped into four sets of enablers, namely, macroeconomic, geo-economic, strategic and geopolitical. The national participation index (G-NPI) has been calculated using the graph theoretic modeling approach. Findings: Besides identifying the factors of a developing country's participation in the GVC and grouping them as enablers, the paper considers the case of India as an example and assesses the level of interactions within (i.e. among various factors of a given enabler) and among these enablers (leading to a G-NPI value) using graph theory. Practical implications: The findings can be used to calculate G-NPI for different countries to ascertain their potential for participation and also to find the factors(s) which may be deterring their participation in the GVCs. Social implications: This paper can help in policy advocacy to enhance the competitiveness of developing countries and consequently to improve the life of their consumers. Originality/value: This paper introduces the concept of G-NPI and presents a unique way of assessing a developing country's participation in the GVCs through a mathematical modeling approach.